The bending properties of bamboo bundle laminated veneer lumber (BLVL) double beams. (30th August 2016) - Chen, Fuming; Jiang, Zehui; Wang, Ge; Li, Haidong; Simth, Lee M.; Shi, Sheldon Q.
Highlights: Large span bamboo bundle laminated veneer lumbers (BLVLs) were prepared by combining the prepress densification process. Mechanical performances of the intermittent hot joints and adjacent positions of large span BLVLs were investigated. A new type of BLVL double-beam members was developed and their bending properties including ultimate load, static bending strength and strain distribution were systematically analyzed. Abstract: Large span bamboo bundle laminated veneer lumbers (BLVLs) were prepared by combining the prepress densification process and the intermittent hot press process. Their mechanical performances of the intermittent hot joints and adjacent positions were also investigated. Based on this, a new type of BLVL double-beam members was developed and their bending properties including ultimate load, static bending strength and strain distribution were systematically analyzed by comparing with other double beams with different members. The results showed that large span BLVLs could be well prepared by intermittent hot press process and its mechanical properties could meet the requirements of 160-E superior products according to Chinese national standard GB/T 17657-2013. Besides, the values for the cross-section flexural rigidity and bending modulus of BLVL double beams were extremely high. Bamboo-wood composites (BWC) double beams with more ductility coefficient had a great ability of plastic deformation. For these double beams, the cross-section stiffness was the first factor which to be considered and optimized and the change of the strain along thickness direction was linear, which was in line with the hypothesis theory of bending plane of materials. This study was finally beneficial to design, manufacture, and application of bamboo-based structural engineering materials with lightweight, low cost, and excellent mechanical performances by supplying financial data support.